Digitalisering av arbeidsflyt på sykehus – konsekvenser for legers arbeidshverdag - Lotherington, Ann Therese; Obstfelder, Aud (Nordisk tidsskrift for helseforskning, 2015)
Digitization of workflow in hospitals – consequences for physicians’ everyday work practices The article analyses digitization of hospital work with Electronic Patient Record (EPR) as example. The analytical perspective is Science and Technology Studies (STS), and scientific methods are survey and in-depth interviews. Survey data indicate that physicians consider themselves as competent users of EPR. Yet they experience stress by digitization. Interview data show that physicians use the EPR both for administrative and clinical purposes, that standards and procedures for use of EPR are becoming increasingly important for everyday practice, and that actors other than physicians determine how the system can be adapted and changed. The consequences are that physicians’ autonomy is reduced and that they loose control over own work situation. These changes are results of complex interaction at the hospital. If physicians want to regain influence, they must engage in the interaction but also accept that the final result might go beyond their own imagination and control.